Implementasi Manajemen Sarana Prasarana Di MTs Salafiyah Syafi’iyah Seblak Jombang - Hani Adi Wijono; A Andri Riyadi (Islamic Education Management Study Program of STIT al Urwatul Wutsqo Jombang, East Java, Indonesia, 2023)
Educational infrastructure means equipment and supplies that are directly used and support the educational process, particularly the teaching and learning process, such as buildings, classrooms, tables, and chairs, as well as teaching tools and media. While what is meant by educational infrastructure are facilities that indirectly support the course of the educational process, such as yards, gardens, parks, and schools, if used directly for the teaching and learning process, such as school gardens for teaching biology or school yards as sports fields, they are components of an educational tool. Educational facilities and infrastructure are also often referred to as school facilities or school equipment. Based on the data analysis that has been done, five conclusions are obtained as follows: First, planning for the procurement of facilities and infrastructure needs at MTs Salafiyah Syafi'iyah Seblak Jombang has been arranged. In accordance with the provisions in the plan, in the procurement of facilities, it will also adjust the real needs, which are the most important, to take precedence over both learning tools and buildings, and so on. Procurement activities only use budgeted BOS funds. In the three stages of using, using, or using the existing facilities and infrastructure at MTs Salafiyah Syafi'iyah Seblak Jombang, there are no official procedures or written rules in the use of facilities and infrastructure because all Madrasah residents have the same rights to use existing facilities and infrastructure according to individual needs